2011
DOI: 10.1177/0017896911407054
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology, diabetes and culturally and linguistically diverse communities: A case study with elderly women from the Vietnamese community

Abstract: Objective: To report the processes and outcomes of a case study on digital technology, diabetes and culturally and linguistically diverse (CALD) communities. Design: The qualitative study was based on a literature review, consultations and testing of a framework through workshops and an interactive information session. Setting: Consultations, workshops and an information session conducted in western regions of Melbourne, Victoria, Australia. Method: A framework was designed to address the needs of CALD comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The ICT has been seen to provide a convenient and effective approach to communicate with others, and it also has assisted the older adults in receiving information that interests them. Especially the older adults who have been experiencing some illness gain benefit from the resources provided by peer groups, which are credible and updated regularly (Fokkema & Knipscheer, 2007;Cresci & Jarosz, 2010;Pan & Jordan-Marsh, 2010;Näsi, Räsänen, & Sarpila, 2012;O'Mara, 2012;Choi & Dinitto, 2013;Heart & Kalderon, 2013;Tsai, Shillair, Cotten, Winstead & Yost, 2015;Hall, Bernhardt, Dodd & Vollrath, 2015). The emotional support among peer group members has also been a positive impact of using ICT (Gustafson et al, 2015).…”
Section: The Information and Communication Technology Adoption Of Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICT has been seen to provide a convenient and effective approach to communicate with others, and it also has assisted the older adults in receiving information that interests them. Especially the older adults who have been experiencing some illness gain benefit from the resources provided by peer groups, which are credible and updated regularly (Fokkema & Knipscheer, 2007;Cresci & Jarosz, 2010;Pan & Jordan-Marsh, 2010;Näsi, Räsänen, & Sarpila, 2012;O'Mara, 2012;Choi & Dinitto, 2013;Heart & Kalderon, 2013;Tsai, Shillair, Cotten, Winstead & Yost, 2015;Hall, Bernhardt, Dodd & Vollrath, 2015). The emotional support among peer group members has also been a positive impact of using ICT (Gustafson et al, 2015).…”
Section: The Information and Communication Technology Adoption Of Older Adultsmentioning
confidence: 99%
“…The health related information has usually been accessed from health-related internet sites (Heart & Kalderon, 2013) and the e-health service of the local authority (Hall, Bernhardt, Dodd, & Vollrath, 2015;Levy, Janke & Langa, 2014). Older adults who have been suffering chronic illness have the possibility to get specific information on their disease (O'Mara, 2012).…”
Section: Improving the Quality Of Life Through The Use Of Ictmentioning
confidence: 99%
“…While a vast amount of literature exists describing interventions to promote DSM, very few studies have been conducted in Vietnamese populations. Only two intervention studies, one from the United States (Wennerstrom et al, 2015) and one from Australia (O’Mara et al, 2012) were identified in this review. Both utilized community-based participatory research methods and included a small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the scant number of studies that have tested DSM interventions among Vietnamese populations and the further limitations of self-reported data and cross-sectional study designs within these studies, it remains unknown whether intervention delivery by CHWs is effective in improving population health outcomes. Wennerstrom et al (2015) and O’Mara et al (2012) reported intervention approaches did not report specific theoretical foundations of the interventions, yet their community-based approaches indicate the importance of assuring linguistic and cultural congruence in intervention development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation